Evaluation of molecular parameters: Viscosity variation method - Murthy, , MBR; Patil,, RL; Dayasagar, , BS (2003)
A new method of evaluating dipole moment of a polar molecule in a non-polar solvent by viscosity variation is proposed. This method needs dilute solution of only one concentration and will be quite useful to evaluate molecular parameters of newly synthesized compounds.